Managing water locally: an inquiry into community- based water resources management in fragile states - Day, St John (Cranfield University, 2016)
Water resources in many parts of the world, but particularly in Africa, face multiple pressures. These growing pressures, along with rainfall variability, pose significant risks to water resources and livelihoods. Over the past two decades the concept of Integrated Water Resources Management (IWRM) has been presented as a panacea, but subscription to this model has not delivered the results expected. Despite a massive endeavour there is extensive evidence that IWRM remains difficult to implement, particularly in fragile states. In contrast, at local level the responsibility of communities to manage water supply systems forms a central component of Water, Sanitation and Hygiene (WASH) sector policy. But WASH programmes are focused primarily on the supply of services, and not enough on water resources. Consequently, remarkably little has been written about the role of communities in monitoring and managing water resources. Also, few studies have examined the transitions fragile government institutions need to undertake to move from one (inferior) situation, to a much better one. This study used Action Research (AR) to investigate the role community-based institutions can play in monitoring water resources, alongside government authorities. Initial field research was conducted in Darfur and Niger before further work in Burkina Faso and Sierra Leone. It found that communities could monitor water resources with high degrees of success; however, continued external support is also required from responsible government institutions. Community-Based Water Resources Management (CBWRM) is considered a realistic and plausible approach for strengthening the water component in WASH programmes. This research argues that in fragile states there is greater potential to develop national water security plans from local- level initiatives. Adopting a “localised” approach is particularly important for countries that face the pervasive obstacles of short rainfall seasons: negligible hydrometeorological monitoring, limited water infrastructure and weak institutions. CBWRM warrants greater attention from the WASH sector and further research is needed to identify how effectively communities can manage water resources and scale up this approach once Water Resource Assessments (WRAs) have been conducted.